Smart thermal management of photovoltaic systems: Innovative strategies - Kaovinath, Appalasamy; Rizalman, Mamat; Sudhakar, K. (AIMS Press, 2025)
The efficiency of photovoltaic (PV) panels is significantly affected by environmental factors such as solar irradiance, wind speed, humidity, dust accumulation, shading, and surface temperature, with thermal buildup being the primary cause of efficiency degradation. In this review, we examined various cooling techniques to mitigate heat accumulation and enhance PV panel performance. A comprehensive analysis of active, passive, and hybrid cooling strategies is presented, including heat pipe-based cooling, heat sinks, holographic films, nanofluids, phase change materials (PCM), thermoelectric, biomaterial-based, and hybrid cooling systems. The effectiveness of these techniques in reducing surface temperature and improving electrical efficiency was assessed. Notably, heat pipe cooling and hybrid PCM-thermoelectric systems demonstrated the most promising improvements, with some methods achieving temperature reductions exceeding 40 °C and efficiency enhancements over 15%. Future research directions include developing advanced nanofluid formulations, optimizing the design of heat pipes and heat sinks, integrating multi-functional coatings, and enhancing the real-world durability of cooling materials for inventing innovative, sustainable, and eco-friendly cooling systems. By providing a structured evaluation of emerging PV cooling techniques, this study a valuable resource for researchers and engineers striving to improve solar energy efficiency, reduce thermal losses, and advance the sustainability of photovoltaic technologies.